From Farm to Fork: Persistence of Clinically Relevant Multidrug-Resistant and Copper-Tolerant Klebsiella pneumoniae Long after Colistin Withdrawal in Poultry Production - Mourão, Joana (2023)
Concerns about colistin-resistant bacteria in animal food-environmental-human ecosystems prompted the poultry sector to implement colistin restrictions and explore alternative trace metals/copper feed supplementation. The impact of these strategies on the selection and persistence of colistin-resistant Klebsiella pneumoniae in the whole poultry production chain needs clarification. We assessed colistin-resistant and copper-tolerant K. pneumoniae occurrence in chickens raised with inorganic and organic copper formulas from 1-day-old chicks to meat (7 farms from 2019 to 2020), after long-term colistin withdrawal (>2 years). Clonal diversity and K. pneumoniae adaptive features were characterized by cultural, molecular, and whole-genome-sequencing (WGS) approaches. Most chicken flocks (75%) carried K. pneumoniae at early and preslaughter stages, with a significant decrease (P < 0.05) in meat batches (17%) and sporadic water/feed contamination. High rates (>50%) of colistin-resistant/mcr-negative K. pneumoniae were observed among fecal samples, independently of feed. Most samples carried multidrug-resistant (90%) and copper-tolerant (81%; silA and pcoD positive and with a MICCuSO4 of ≥16 mM) isolates. WGS revealed accumulation of colistin resistance-associated mutations and F type multireplicon plasmids carrying antibiotic resistance and metal/copper tolerance genes. The K. pneumoniae population was polyclonal, with various lineages dispersed throughout poultry production. ST15-KL19, ST15-KL146, and ST392-KL27 and IncF plasmids were similar to those from global human clinical isolates, suggesting chicken production as a reservoir/source of clinically relevant K. pneumoniae lineages and genes with potential risk to humans through food and/or environmental exposure. Despite the limited mcr spread due to the long-term colistin ban, this action was ineffective in controlling colistin-resistant/mcr-negative K. pneumoniae, regardless of feed. This study provides crucial insights into the persistence of clinically relevant K. pneumoniae in the poultry production chain and highlights the need for continued surveillance and proactive food safety actions within a One Health perspective. IMPORTANCE The spread of bacteria resistant to last-resort antibiotics such as colistin throughout the food chain is a serious concern for public health. The poultry sector has responded by restricting colistin use and exploring alternative trace metals/copper feed supplements. However, it is unclear how and to which extent these changes impact the selection and persistence of clinically relevant Klebsiella pneumoniae throughout the poultry chain. We found a high occurrence of copper-tolerant and colistin-resistant/mcr-negative K. pneumoniae in chicken flocks, regardless of inorganic and organic copper formulas use and a long-term colistin ban. Despite the high K. pneumoniae isolate diversity, the occurrence of identical lineages and plasmids across samples and/or clinical isolates suggests poultry as a potential source of human K. pneumoniae exposure. This study highlights the need for continued surveillance and proactive farm-to-fork actions to mitigate the risks to public health, relevant for stakeholders involved in the food industry and policymakers tasked with regulating food safety.